75 What is the role of a pharmacist in a parkinson's multidisciplinary team?. (3rd November 2019) - Dhap, J; Morgan, J; Breen, L; Powell, C
Abstract : Worcestershire Integrated Neurological Rehabilitation Service (WINRS) recognised their Parkinson's disease (PD) caseload was increasing and more patients were presenting with complex care needs. A comparison of caseloads and referral times between healthcare professionals (HCPs) identified areas were workload was duplicated. Patients were also waiting longer for assessments with individual HCPs. WINRS collaborated with the Trusts Pharmacy Team to pilot PD multidisciplinary team (MDT) clinics. Patients attend a PD MDT with the PD specialist nurse (PDSN), physiotherapist, occupational therapist (OT) and pharmacist in one single clinic to formulate a collaborative care plan. The PDSN leads the review using an agreed PD assessment tool ensuring a systematic review is conducted. Patients are given the opportunity to discuss their care needs and benefits from the expert knowledge of each HCP. The integrated care approach minimises duplication of workload and reduces waiting time referrals. The pharmacist supports the PDSN with accurate medication history, medication review and any other medication-related problems. The utilisation of pharmacists' specialist knowledge in long term conditions (LTCs) is highly recommended in national guidelines. However, a systematic literature search was conducted in 2018 using healthcare databases. The literature search identified 17 PD MDT peer-reviewed studies. The MDTs identified varied both in the number and the type of HCPs. Physiotherapists and OTs (n=16) were included most often and PDSN (n=8) included sometimes. None of the studies identified involved a pharmacist. Pharmacists have shown benefits when working in MDTs for other LTCs; however, their role in PD MDT is not researched enough. Research is underway to identify the role of a pharmacist in a PD MDT. We anticipate the research will show that patients, carers and HCPs will prefer a more inclusive PD MDT with a pharmacist resulting in improved patient care.